DETERMINANTS OF FOREIGN DIRECT INVESTMENT IN ORGANIZATION OF THE ISLAMIC COOPERATION COUNTRIES: DOES FINANCIAL DEVELOPMENT MATTER? - Zulkifli Zulkifli; Alan Budi Kusuma; Andi Ika Fahrika; Muhammad Adnan Azzaki (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
A study on the factors influencing foreign direct investment (FDI) was started by the Islamic Cooperation countries, the majority of which are developing nations, due to the significance of capital flows for these nations. The present study employs an institutional quality framework, green economic policies, and the function of financial development to evaluate the components that effect foreign direct investment (FDI). The results of this research demonstrate that institutional changes and green economic policies stimulate foreign investment. Several institutional metrics, including government performance, the rule of law, political stability, and regulatory quality, have highly positive outcomes, while electoral accountability and preventing corruption have negative and minor consequences. Furthermore, elements of the green economy including human capital, natural resources, and environmental laws have a big impact on foreign investment. These results also suggest that the growth of the financial sector can boost the impact of institutional quality and the green economy on the attraction of foreign investment. The conclusions of this study demonstrate that investors examine institutional integrity, the green economy, and financial development when making investment decisions.